Analisis Penerapan Hukum Dan Pertanggungjawaban Pidana Illegal Fishing Dalam Putusan No.107/PID.B/2009/PN.TPI.RNI - Eko Nurisman; Rahmi Ayunda (Fakultas Hukum, Universitas Internasional Batam, 2016)
Lies in the strategic area made Riau Islands province became an attractive destination for foreign vessel to do illegal fishing. Riau Island Province especially Natuna rank at the first place in Indonesia as the region which has the fishes being stolen the most. This thesis is the result of research on how the application of the law and the criminal liability toward the doer of illegal fishing according to Tanjung Pinang’s fisheries court decision number 107/Pid.B/2009/PN.TPI.RNI. Type of this thesis is normative legal research, the data that used is in the form of secondary data, which consist of both primary and secondary legal materials. The author collecting the data by doing library research and interview. Once all the data is collected, the data is then processed and analyzed. The qualitative method was used to group the data point by the studied aspects. Further conclusions drawn related to this study, then described descriptively. From this research the author can conclude that Tanjung Pinang’s fisheries court judges in performing the application of the law for those involved in illegal fishing is still not quite right. There is a verse that should be charged to the defendant but not enforced, while for terms of criminal liability can be concluded that upon the defendant can held to be responsible, it is based on the elements of criminal responsibility that has fulfilled. with this fulfillment have consequences the defendant should be declared guilty and have to be responsible for his actions to undergo criminal penalties.